Interpretations of Adam Smith through the Austrian School of Economics - Reynolds, Wesley (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
Even accepting the scientific rationality and the theory of laissez-faire advocated by Adam Smith, economists of the Austrian School broadened the scope of Economic Science while they disrupted the objective assumptions of Enlightenment, adopting a subjective view of human action of economic agents. Throughout the text the author presents several points of divergence and convergence between the ideas of Adam Smith and thinkers as Carl Menger, Eugen von Böhm-Bawerk, F. A. Hayek, Henry Hazlitt, Ludwig von Mises and Murray N. Rothbard.